Long-term treatment with senolytic drugs Dasatinib and Quercetin ameliorates age-dependent intervertebral disc degeneration in mice - Emanuel J. Novais (Nature Portfolio, 2021)
Intervertebral disc degeneration is a leading cause of chronic back pain and disability. Here the authors show that long term treatment with senolytic compounds Dasatinib and Quercetin reduces disc senescence burden and ameliorates age-dependent degeneration in mice.